Politik Hukum Otonomi Daerah di Bidang Kesehatan Saat Pandemi Covid-19 di Provinsi Lampung - Kamal Fahmi Kurnia; Harli Marcelino (Journal on Education, 2023)
Since ancient times until now, the arrangement of power from the central government to regional governments has always been different. Until now the central government has given authority to regional governments in the form of regional rights, powers and obligations to regulate and manage their own households in accordance with applicable laws and regulations which is called regional autonomy. Since early March 2020, Indonesia has been hit by the Corona Virus Disease (Covid-19), which has even been declared a national disaster because the spread of this virus is so fast that it can even cause death. Lampung Province as the gateway to Sumatra is very vulnerable to exposure to the Covid-19 virus where there were 77,148 cases during 2020-2023 both those who recovered and died. This article discusses the legal politics of regional autonomy in the era of the Covid 19 pandemic in the health sector. By using a qualitative descriptive research method that describes existing phenomena or facts, both natural and human engineering. This study pays more attention to the quality, characteristics, and interrelationships between activities. Referring to the mandate of regional autonomy where district/city scale health affairs are decentralized to district/city regional governments and provincial scale health affairs are decentralized to provincial regional governments, so that in handling Covid-19 in Lampung Province the rights and authorities of autonomy can be implemented. Regarding the handling of the Covid-19 pandemic in Lampung Province, the roles and functions of the local government have been quite optimal, the health budget and human resources must be increased again so that regional autonomy in the health sector can run more optimally.